New substances, new concerns - Selective Androgen Receptor Modulators - Antić, Dušan (Archives of Pharmacy, 2022)
Many athletes have used selective androgen receptor modulators (SARMs) recently. They are experimental drugs which are being tested as a potential therapy for increasing both muscle and bone strenght in the elderly or for patients who need it for medical reasons. SARMs include various substances, such as ligandrol, ostarin and testolone. Up to now there are no completed studies which would confirm their positive effects on human body. SARMs, as sports supplements, can be often bought online. Among other things, they are stated to increase muscle growth and strenght, make fast recovery after injuries, without side effects of steroids. However, there are no safety studies of SARMs. The FDA has released data linking the usage of SARMs with both liver and heart failure, myocardial infarction, stroke. In addition, supplements often contain SARMs in combination with hormone and metabolic modulators, such as GW1516 (also known as cardarine or endurobol). GW1516 was originally development as a treatment for diabetes, obesity and cardiovascular disease. It was discontinued later after it was linked to the rapid development of cancer during trials on mice.When it comes to sport, as a doping in sport SARMs can be found on the WADA Prohibited List, in section S.1. Anabolic Agents. If an athlete would have a doping positive sample on SARMs, he or she would be punished with 2 to 4 years period of ineligibility.